Morphological characteristic of Fusarium spp. in several highlands of North Sumatera. Issue 3 (June 2021) - Minarni; Hasanuddin; Ginting, J
Abstract: Fusarium spp. is a genus of fungi that causes disease in many plants so that special attention, handling and control is needed for this pathogen. Morphological observations are needed to provide an overview of macroscopic and microscopic morphological variations that be used as basic information in the development of a Fusarium spp. control program. The research aims to determine the morphological characteristics of Fusarium spp. in several highlands of North Sumatra. The research was conducted at the Laboratory of Plant Diseases, Faculty of Agriculture, Universitas Sumatera Utara, Medan in September-December 2019. Fusarium spp. isolates obtained from several highlands of North Sumatra were rejuvenated on Potato Dextrose Agar (PDA) medium. All isolates were observed macroscopically and microscopically to determine colony morphology including macroconidium, microconidium and conidiophores. Microscopic morphological observations using a compound microscope. The results showed that Fusarium spp . obtained have almost the same morphology. Microscopic observation showed that there were differences in macroconidia morphology in Fusarium spp isolates found in Tanah Karo District with Simalungun and Dairi Districts.